A Genome Model to Explain Major Features of Neurodevelopmental Disorders in Newborns. (July 2019) - Friedenson, Bernard
The purpose of this study was to test the hypothesis that infections are linked to chromosomal anomalies that cause neurodevelopmental disorders. In children with disorders in the development of their nervous systems, chromosome anomalies known to cause these disorders were compared with foreign DNAs, including known teratogens. Genes essential for neurons, lymphatic drainage, immunity, circulation, angiogenesis, cell barriers, structure, epigenetic and chromatin modifications were all found close together in polyfunctional clusters that were deleted or rearranged in neurodevelopmental disorders. In some patients, epigenetic driver mutations also changed access to large chromosome segments. These changes account for immune, circulatory, and structural deficits that accompany neurologic deficits. Specific and repetitive human DNA encompassing large deletions matched infections and passed rigorous artifact tests. Deletions of up to millions of bases accompanied infection-matching sequences and caused massive changes in human homologies to foreign DNAs. In data from 3 independent studies of private, familial, and recurrent chromosomal rearrangements, massive changes in homologous microbiomes were found and may drive rearrangements and encourage pathogens. At least 1 chromosomal anomaly was found to consist of human DNA fragments with a gap that corresponded to a piece of integrated foreign DNA. Microbial DNAs that match repetitive or specific human DNA segments are thus proposed to interfere with the epigenome and highly active recombination during meiosis, driven by massive changes in human DNA-foreign DNA homologies. Abnormal recombination in gametes produces zygotes containing rare chromosome anomalies that cause neurologic disorders and nonneurologic signs. Neurodevelopmental disorders may be examples of assault on the human genome by foreign DNAs at a critical stage. Some infections may be more likely tolerated because they resemble human DNA segments. Even rare developmental disorders can be screened for homology to infections within altered epigenomes and chromatin structures. Considering effects of foreign DNAs can assist prenatal and genetic counseling, diagnosis, prevention, and early intervention.